2010
DOI: 10.4103/0256-4947.72263
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of skin diseases in the Qassim region of Saudi Arabia: What the primary care physician should know

Abstract: BACKGROUND AND OBJECTIVES:Epidemiological studies to determine the burden of skin diseases are important for proper health care planning. The purpose of this study was to find the pattern of skin diseases in our patients attending university-affiliated dermatologic clinics in the Qassim region.METHODS:We conducted a prospective study of all Saudi patients attending the Qassim University Medical College-affiliated dermatology clinics of the Ministry of Health for a period of 12 months from 1 March 2008 to 28 Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
8
21
2
Order By: Relevance
“…However, some studies conducted here in Saudi Arabia have found the opposite, with males being significantly more prominent than females in other regions; this may be due to cultural factors that prevent females from seeing doctors, or male lifestyles in these areas that make them more prone to skin diseases. [9][10][11][12] In general, the pattern of skin diseases in the area studied, as shown in Figure 2, is identical to what has been found in previous studies all around Saudi Arabia. However, in contrast with these previous studies, atopic eczema was 1369 also the most frequent disease, but the percentage of eczema was much higher in our area, while viruses were the commonest cause of infections in other areas, but in our region fungal infection was more prevalent.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Psupporting
confidence: 69%
See 2 more Smart Citations
“…However, some studies conducted here in Saudi Arabia have found the opposite, with males being significantly more prominent than females in other regions; this may be due to cultural factors that prevent females from seeing doctors, or male lifestyles in these areas that make them more prone to skin diseases. [9][10][11][12] In general, the pattern of skin diseases in the area studied, as shown in Figure 2, is identical to what has been found in previous studies all around Saudi Arabia. However, in contrast with these previous studies, atopic eczema was 1369 also the most frequent disease, but the percentage of eczema was much higher in our area, while viruses were the commonest cause of infections in other areas, but in our region fungal infection was more prevalent.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Psupporting
confidence: 69%
“…This may be caused by the geographical location of Qunfudah city; being beside the sea, there is a high level of humidity, and the hot climate year-round creates a viable breeding ground for fungal infections. [9][10][11][12] Infections were more common in males; we believe this is because males' lifestyle cause them to have more exposure to heat and humidity, as well as contact with animals. However, females had more hair disorders, which we believe are induced by pregnancy and breastfeeding, or perhaps because they use hair dyes more often than males, that contain chemicals that could lead to hair damage; a recent study conducted in South India supports this hypothesis.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations were recorded in cases of pigmentary lesions, papulosquamous disorders and protozoal infections. [11]While Abdulrahman et al (2008) reported that during the five year period (2001)(2002)(2003)(2004)(2005), a total of 58450 cases were seen at the dermatological clinics of Riyadh Military Hospital. The incidence of dermatological diseases was more in female patients 34123 (58.38%) than male patients 24327 (41.62%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This observation correlates well with other studies that report allergic skin diseases as the most common cause to seek care from a health provider. (4)(5)(6)(7) Among the allergic skin diseases observed, dermatitis was predominant. The breakdown of dermatitis subtypes has revealed a high frequency of contact dermatitis (33.9%).…”
Section: Discussionmentioning
confidence: 99%